POLITICAL ELITE AS A SUBJECT OF STATE BUILDING IN CONDITIONS OF UKRAINIAN SOCIETY TRANSFORMATION - Козловець, М. А. (Вісник НЮУ імені Ярослава Мудрого: Серія: Філософія, філософія права, політологія, соціологія, 2017)
The article based on analysis of historical experience and contemporary practice of Ukraine investigates the role of the political elite in the process of state building, social changes. Ukrainian historical tragedy is conditioned by the constant disconnect of elite generations, loss of tradition of sacrificial service to the people when within centuries alien elite was impose to Ukraine and its regions with different principles and basis of life or- ganization, culture and traditions. The author sees the dependence of the formation and strengthening of Ukrainian statehood on their national elites as the fact and concludes that in the latest phase of independence Ukraine emtered together with the quasi-elite that is not able to realize the national idea in its entirety. Civil society and a legal democratic state development condition the necessity of the political elite as a socially oriented insti- tution. The article proves the necessity of the formation of a new generative elite – the elite of merit (meritocracy), liability elite which is capable to ensure effective governance in terms of rapid political and socio-economic changes, skillfully regulate all aspects of public life. Ukrainian political elite should become a part of the European elite, identify themsecves with the relevant values. Distinguishing the concept of «establishment» and «political elite», the author argues that the transformation taking place in the modern Ukrainian society forms the social order to a new type of political elite that could be the subject of social changes, they ini- tiator and coordinator, to be responsible for reforming the country, their professional and managerial ability. The process of elitarization of the political class is seen not only as an important attribute of state-building, but also as the basis of political modernization. Particular attention is paid to the peculiarities of the formation of political Elitas, their specific function in the system of social relations. Describing the basic requirements for modern elitagenesis process, the author offeres the successful way to implementation of function of the subject of social transformation and qualitative changes, including: the presence of political pluralism, changes in the electoral system to ensure equal competition of potential elites; ensurance of a certain balance, compromise, the balance of the differ- ent social forces, ie the formation of joint consensus-facial features of the political elite; maximum openness of elite at all levels, constant replenish with the trained professionals and functionally capable people; update of the mentality of the political elite, understand-ing that social changes need serious information support and elicit people, civil society institutions; the availability of permanent democratic control over the activities of au- thorities by the public, the media, political parties and organizations; consolidation of the various sectors of society, harmonizing their social interests and achievement of coopera- tion and close cooperation of all forces in society; a clear rule of law, democratic norms and procedures necessary and required for normal functioning of the constitutional state and civil society.